Increasing Learning Achievement of CNC Machining through the Use of a CNC Lathe Machine Simulator for Class XI Students of Mechanical Engineering at SMK Negeri 6 Samarinda Academic Year 2022 - Bahri, Abdul (PT Literasi Nusantara Publisher, 2022)
This study aims to: (1) increase the activity of class XI TP SMK Negeri 6 Samarinda in CNC subjects using CNC lathe simulator media, and (2) improve student achievement in CNC subjects using CNC lathe simulator media. This research is classroom action research with the Kemmis model & Mc Taggart. This research lasted for three rounds (cycles). The research procedure starts from action planning, action implementation, observation, and reflection. The subjects of this study were students of class XI at SMK Negeri 6 Samarinda, which consisted of 30 students. The instruments used in this study were observation sheets and learning achievement tests. Data about student activity was obtained through class observation and the results of the observations were processed in group and individual processing to compare the level of student activity in each cycle. Data on learning achievement was obtained through exams and analyzed to compare exam results in each cycle. The results of the study show that learning using a CNC lathe machine simulator media can increase student activity and achievement during the learning process. The pattern of learning carried out in cycle I was by lecture method, question and answer, and using power point media which was very appropriate in the early stages to convey material about programming parts. This is evidenced by the number of students who were very active during learning, namely 11 students or 37% with learning achievement reaching 6.65. The pattern of learning carried out in cycle II is to provide exercises and assignments with high intensity which can increase student activity by 16 students or 53% accompanied by learning achievement of 7.34. learning patterns with problem solving applied in cycle III were able to increase student activity, namely to 21 students or 67% followed by an increase in learning achievement reaching 7.92.